Examining the Factors Affecting SMEs Performance: The Mediating Role of Social Media Adoption - Salomi, J.J.; Tharshiga, P. (Sri Lanka Finance Association., 2023)
Small and Medium-Sized Enterprises (SMEs) are considered the backbone of any successful and thriving economy. Increasing globalization and rapid digitization across industries have led to greater international competition. Furthermore, innovation has created challenges and opportunities for SMEs, and they have recently been attracted to social media applications to reach a larger audience, improve their relationship with potential customers, and retain existing customers. However, scant focus has been devoted to comprehensively understanding the adoption of social media in the SMEs context in developing countries. Many SMEs are adopting social media platforms to contact potential customers and provide services. After the end of the civil war 2009 and the COVID-19 pandemic, people from the Northern Province, especially in Jaffna, started SMEs, which should be run on virtual and physical markets for business survival. Therefore, this study examines the effect of social media adoption on SMEs performance in Jaffna district using an integration of the TOE (Technology, organization, environment) framework. The study employed a quantitative approach, and a closed-ended questionnaire was used to gather the data. The normality and reliability of the measurement, correlation analysis, and regression analysis were established to test the study's hypotheses. Also, the Sobel test was used to test the mediating effect. The results revealed that technological, organizational, and environmental factors positively impact SMEs' performance. The results also revealed that social media adoption significantly influences the mediating role of SMEs' performance. In addition, media adoption mediates the relationship between technological, organizational, and environmental factors and SMEs' performance.
Keywords: Small and medium-sized enterprises; SMEs performance; Social media; Social media adoption; TOE framework